Measuring the Resistivity of Titanium Minerals in a Corona Field (40c01edc-ab2e-46a3-b780-08ab00456749) - Mary M. Ng; Peter N. Holtham (International Mineral Processing Congress, 2003)
"Resistivity measurements of minerals in the laboratory are commonly made with a low DC voltage source. Common test voltages specified in the ASTM Standard D257 are 100, 250, 500, 1000, 2500, 5000, 10000 and 15000 V, however 100 and 500 V are the most frequently used. Resistivity results obtained in the laboratory have been used to infer the electrical behaviour of minerals undergoing electrostatic separation. However because the voltages employed in electrostatic separation in the plant are of the order of thousands of volts, typically greater than 15000 V, whether the laboratory results are applicable as a predictor of plant performance is a critical question. It is unclear whether resistivity values taken at a low voltage are characteristic of those seen in electrostatic separation, in which the minerals are exposed to a much higher voltage. No definitive answer could be found in the literature.In this work, the resistivities of zircon, rutile and ilmenite were measured in a corona field for the first time. The measurement principle was based on a technique developed to measure fly ash resistivity in electrostatic precipitators, however the test apparatus and findings are novel.Resistivities of rutile and zircon were found to be easy to measure. The values measured in a corona field were several orders of magnitude less than those obtained with a dc voltage of 100 V. Evidence of back corona was observed with zircon. When the voltage drop was greater than the sample layer could withstand a localised electrical stress developed, resulting in a voltage breakdown, at which point a sudden surge of corona current (back corona) was detected in the sample layer. Rutile, on the other hand, exposed to the same conditions as that of zircon (i.e. same temperature and applied voltage) did not exhibit any sign of back corona. Its resistivity across the range of test voltages (14 to 33 kV) remained fairly constant."